A new myxozoan species Henneguya unitaeniata sp. nov. (Cnidaria: Myxosporea) on gills of Hoplerythrinus unitaeniatus from Mato Grosso State, Brazil - Úngari, Letícia Pereira [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; da Silva, Reinaldo José [UNESP]; Santos, André Luiz Quagliatto; de Azevedo, Rodney Kozlowiski; O’Dwyer, Lucia Helena [UNESP] (Springer Nature, 2019)
On the basis of morphological and molecular analyses, a new myxozoan parasite is described from the gills of the fish Hoplerythrinus unitaeniatus, collected in the municipality of Nova Xavantina, Mato Grosso State, Brazil. Plasmodia of Henneguya unitaeniata sp. nov. were oval and whitish and were found surrounded by collagen fibers forming plasmodia wall between gill filaments on the gill arch. The spores were ellipsoidal with two similar polar capsules. Morphometric analysis showed a total spore mean length of 23.8 ± 1.5 μm, spore body mean length of 14.5 ± 0.7 μm, caudal appendage mean length of 10.3 ± 1.4 μm, thickness mean length of 4.3 ± 0.3 μm, polar capsule mean length of 4.2 ± 0.5 μm, polar capsule mean width of 1.8 ± 0.3 μm, spore mean width of 4.8 ± 0.4 μm, and 4–5 polar filament coils. Phylogenetic analysis showed Henneguya unitaeniata sp. nov. as a basal species in a subclade formed by myxozoans that parasitize bryconid fishes.
Keywords: Erythrinidae; Histopathology; Myxobolidae; Phylogeny; SSU rDNA